Effect of the inhaled PDE4 inhibitor CHF6001 on biomarkers of inflammation in COPD - Dave Singh; Kai Michael Beeh; Brendan Colgan; Oliver Kornmann; Brian Leaker; Henrik Watz; Germano Lucci; Silvia Geraci; Aida Emirova; Mirco Govoni; Marie Anna Nandeuil (2019)
CHF6001 is a novel inhaled phosphodiesterase-4 inhibitor. This Phase IIa study assessed the effects of CHF6001 on markers of inflammation in induced sputum and blood in patients with chronic obstructive pulmonary disease (COPD). This was a multicentre, three-period (each 32 days), three-way, placebo-controlled, double-blind, complete-block crossover study. Eligible patients had COPD, chronic bronchitis, and were receiving inhaled triple therapy for ≥2 months. Patients received CHF6001 800 or 1600 μg, or matching placebo twice daily via multi-dose dry-powder inhaler (NEXThaler). Induced sputum was collected pre-dose on Day 1, and post-dose on Days 20, 26 and 32. Blood was sampled pre-dose on Day 1, and pre- and post-dose on Day 32. Of 61 randomised patients, 54 (88.5%) completed the study. There were no significant differences between groups for overall sputum cell count, or absolute numbers of neutrophils, eosinophils or lymphocytes. CHF6001 800 μg significantly decreased the absolute number and percentage of macrophages vs placebo. In sputum, compared with placebo both CHF6001 doses significantly decreased leukotriene B4, C-X-C motif chemokine ligand 8, macrophage inflammatory protein 1β, matrix metalloproteinase 9, and tumour necrosis factor α (TNFα). In blood, both CHF6001 doses significantly decreased serum surfactant protein D vs placebo. CHF6001 1600 μg significantly decreased TNFα ex-vivo (after incubation with lipopolysaccharide). The data from this study show that CHF6001 inhaled twice daily has anti-inflammatory effects in the lungs of patients with COPD already treated with triple inhaled therapy. The study is registered on ClinicalTrials.gov ( NCT03004417 ).